2001
DOI: 10.1002/hed.1107
|View full text |Cite
|
Sign up to set email alerts
|

Esthesioneuroblastoma: The impact of treatment modality

Abstract: Surgical resection plus adjuvant radiation therapy yielded the best treatment outcome. More effective chemotherapy agents with a reproducible effectiveness are needed for patients with locally advanced esthesioneuroblastoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
85
0
7

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(95 citation statements)
references
References 23 publications
3
85
0
7
Order By: Relevance
“…For instance, Bailey and Barton (40) found only 8 patients with cervical lymph node metastases (7.2%), not 24 (22%); adjusting for these errors, the cumulative metastatic rate should be 18.8%. Unfortunately this error recurs in recent papers (41).…”
Section: Cervical Lymph Node Metastasesmentioning
confidence: 92%
“…For instance, Bailey and Barton (40) found only 8 patients with cervical lymph node metastases (7.2%), not 24 (22%); adjusting for these errors, the cumulative metastatic rate should be 18.8%. Unfortunately this error recurs in recent papers (41).…”
Section: Cervical Lymph Node Metastasesmentioning
confidence: 92%
“…3,4,8,[11][12][13][14][15] Although the superiority of combined therapy in stage B and C patients has been clearly demonstrated, 3,4,16 several studies did not find a benefit to adding postoperative RT in stage A patients with negative surgical margins. 1,16 Most institutions currently favor craniofacial resection, however, and several studies have shown promising results using less invasive endoscopic sinus surgery.…”
Section: Discussionmentioning
confidence: 96%
“…Overall, risk of local recurrence remains the most consistent feature manifesting in 30% of patients. Cervical node metastasis is known to occur in 23% of cases and is best managed with neck dissection followed by radiotherapy . Currently, there is limited evidence to suggest that elective surgery or radiotherapy is beneficial to patients with N0 disease .…”
Section: Discussionmentioning
confidence: 99%